Recent Advances in Hybrid Nanocomposites for Aerospace Applications - Beatriz Monteiro; Sónia Simões (Metals, 2024)
Hybrid nanocomposites have emerged as a groundbreaking class of materials in the aerospace industry, offering exceptional mechanical, thermal, and functional properties. These materials, composed of a combination of metallic matrices (based on aluminum, magnesium, or titanium) reinforced with a mixture of nanoscale particles, such as carbon nanotubes (CNTs), graphene, and ceramic nanoparticles (SiC, Al2O3), provide a unique balance of high strength, low weight, and enhanced durability. Recent advances in developing these nanocomposites have focused on optimizing the dispersion and integration of nanoparticles within the matrix to achieve superior material performance. Innovative fabrication techniques have ensured uniform distribution and strong bonding between the matrix and the reinforcements, including advanced powder metallurgy, stir casting, in situ chemical vapor deposition (CVD), and additive manufacturing. These methods have enabled the production of hybrid nanocomposites with improved mechanical properties, such as increased tensile strength, fracture toughness, wear resistance, and enhanced thermal stability and electrical conductivity. Despite these advancements, challenges remain in preventing nanoparticle agglomeration due to the high surface energy and van der Walls forces and ensuring consistent quality and repeatability in large-scale production. Addressing these issues is critical for fully leveraging the potential of hybrid nanocomposites in aerospace applications, where materials are subjected to extreme conditions and rigorous performance standards. Ongoing research is focused on developing novel processing techniques and understanding the underlying mechanisms that govern the behavior of these materials under various operational conditions. This review highlights the recent progress in the design, fabrication, and application of hybrid nanocomposites for aerospace applications. It underscores their potential to revolutionize the industry by providing materials that meet the demanding requirements for lightweight, high-strength, and multifunctional components.